Mortality due to rheumatic heart disease in the Kimberley 2001–2010 - Alexandra Hofer; Sarah Woodland; Reeve Carole (Australian and New Zealand Journal of Public Health, 2014)
Abstract Objective: To determine the mortality burden of rheumatic heart disease (RHD) in the Kimberley. Methods: A retrospective medical record audit was conducted for patients identified by the Western Australian (WA) RHD Program as deceased between 2001 and 2010. Patients with documented evidence strongly suggesting or confirming RHD were included in the study. Crude and age‐standardised death rates were calculated. Results: A total of 34 patients were identified as having RHD, 15 of whom died of RHD‐attributable causes and 93% of whom were Aboriginal. The most common causes of death were arrhythmias and heart failure. The mean age at death of Aboriginal people was 41 years. The age‐standardised death rate in Aboriginal people attributable to RHD in the Kimberley was 12.5 per 100,000 people per year, which is 1.6 times the rate of Indigenous Australians nationally. RHD contributed to 342 potential life years lost over the 10‐year period. Conclusion: RHD contributes to significant premature mortality and higher rates of death in Aboriginal people in the Kimberley, which is consistent with other areas of northern Australia. While the recent establishment of the WA RHD Program will endeavour to improve mortality and morbidity due to RHD in the Kimberley, further research and investment is needed to address this disease of socioeconomic disadvantage.